Praktikum iz ginekologije in porodništva – obvezni posegi - Dovnik, Andraž (2024)
Basic Skills in Obstetrics and Gynecology - Mandatory Interventions. This script has been prepared for the students in the sixth year of medical school and contains ali basic skills which come into consideration as part of practical study of obstetrics and gynaecology. The main aim of this course is to obtain practical skills which are needed during everyday clinical work and integrate these skills into theoretical knowledge. This book covers topics such as how to obtain gynaecologic history and mandatory procedures which are done at the inpatient department. Pictures are added for easier understanding. Most of these procedures are done at the clinical department with the help of the attending doctor or nurse. During the course, the student helps in the aseptic theatre and princi ples of asepsis and hygiene in the operating room are described.
Keywords: medical history; pelvic examination; cervical cytology; drawing venous blood; ardiotocography